Improving Students’ reading comprehension through the use of graphic organizers at Military Medical University: An Action Research - Kieu, Thi Van (ĐHNN, 2017)
The focus of this study was on the effects of implementing graphic organizers to teach reading to the students at Military Medical University. The aims of carrying out this action research were two – fold: (1) to investigate the current situation and attit (...)